2012
DOI: 10.1143/jjap.51.04dd06
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Uniformity of Resistive Switching Parameters by Selecting the Electroformation Polarity in IrOx/TaOx/WOx/W Structure

Abstract: A route to improve the uniformity of key resistive switching memory parameters such as SET/RESET voltages, low/high-resistance states as well as switching cycles is demonstrated in an IrO x /TaO x /WO x /W simple resistive memory stack by selecting the electroformation polarity. The various stack layers are confirmed by high-resolution transmission electron microscopy, energy dispersive X-ray sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…[12,27] Although this chemical reaction also leaves abundant oxygen vacancies in the oxide layer, these defects occupy shallower energy levels (from ∼ 0.25 eV to ∼ 0.57 eV) and trend to construct a conductive filament acting as a virtual electrode. [28][29][30] Therefore, resistive switching only happens in the thin TiO 2− zone in this study, as shown in Fig. 4.…”
Section: Introductionmentioning
confidence: 77%
“…[12,27] Although this chemical reaction also leaves abundant oxygen vacancies in the oxide layer, these defects occupy shallower energy levels (from ∼ 0.25 eV to ∼ 0.57 eV) and trend to construct a conductive filament acting as a virtual electrode. [28][29][30] Therefore, resistive switching only happens in the thin TiO 2− zone in this study, as shown in Fig. 4.…”
Section: Introductionmentioning
confidence: 77%
“…30,31) Switching mechanism in the fabricated resistive switch has been explained with the help of slope fitting in I-V graph as reported in the literature. [32][33][34][35] The I-V graph has been drawn in log-log scale for the HRS as shown in Fig. 8.…”
Section: Electrical Characterizationmentioning
confidence: 99%